Wayfinding and signing guidelines for airport terminals and landside - Harding, James R. (ACRP report ;, 2011)
ACRP report 52 is designed to provide airports with the tools necessary to help passengers find their way in and around the airport. The guidelines focus on four areas of the airport: (1) roadways?both on-airport, and off-airport access roads; (2) parking; (3) curbside and ground transportation; and (4) terminal. In addition, the guidelines discuss developing a wayfinding strategy; the use of technology and visual displays; and color, fonts, and sizes.